Synthesis of multivalent polymer–aptamer conjugates with enhanced inhibitory potency - Martin, Jacob T (Int J Nanomedicine, 2018)
PURPOSE: We are interested in designing a modular strategy for creating potent multivalent ligands, which frequently can be used as effective inhibitors of undesired biomolecular interactions. For example, such inhibitors might prevent the self-assembly of bacterial toxins or the attachment of a virus to its host cell receptors. METHODS: We used a biocompatible polyamino acid polymer as a scaffold for grafting multiple copies of an oligonucleotide aptamer (OA). Specifically, the carboxylates on the side chains of polyglutamic acid (PGA) were modified with a thiol-reactive linker, N-aminoethyl maleimide (AEM), and thiol-functionalized OAs were attached to the maleimide moieties. The resulting conjugates were tested for their ability to compete with and inhibit the binding of unconjugated monovalent OAs to the target cell receptor. RESULTS: Multivalent PGA–OA conjugates with low, medium, and high valency were successfully prepared. The varying valency and successful purification to remove unconjugated OAs were confirmed by polyacrylamide gel electrophoresis. The resulting purified conjugates inhibited the binding of unconjugated monovalent OAs, and the measured half maximal inhibitory concentration (IC(50)) values corresponded to a 38–88-fold enhancement of potency on a per-aptamer basis, relative to OA alone. CONCLUSION: Multivalent conjugation of OA ligands has potential as a generally useful way to improve the potency of the interaction between the ligand and its target receptor. We have demonstrated this principle with a known OA as a proof of concept as well a synthetic strategy that can be used to synthesize multivalent conjugates of other OAs.